Estrogen plus progestin increase superoxide dismutase and total antioxidant capacity in postmenopausal women. (June 2015) - Unfer, T. C.; Figueiredo, C. G.; Zanchi, M. M.; Maurer, L. H.; Kemerich, D. M.; Duarte, M. M. F.; Konopka, C. K.; Emanuelli, T.
Abstract Objective This cross-sectional study aimed to evaluate the behavior of blood antioxidant enzymes (superoxide dismutase (SOD), catalase and glutathione peroxidase), plasma total antioxidant capacity and oxidative damage (lipid oxidation and protein carbonyl levels) and their relationship with the serum levels of steroid hormones in premenopausal and postmenopausal women without and with estrogen alone (ET) or estrogen plus progestin therapy (EPT). Methods Blood was collected from four groups of subjects: premenopausal women (n = 24), postmenopausal women without hormone therapy (n = 31), postmenopausal women with ET (n = 12) and postmenopausal women with EPT (n = 16). Results The activities of the different SOD isoforms (CuZnSOD and MnSOD) and the plasma total antioxidant power were significantly higher in the postmenopausal women under EPT than in the postmenopausal women without hormone replacement therapy (HRT). Only CuZnSOD activity was increased in women receiving ET compared to the postmenopausal women without HRT. However, no differences were observed in the levels of lipid or protein oxidation or in the non-enzymatic plasma antioxidants (uric acid and albumin) among the groups. The duration of HRT and serum estrogen levels were positively correlated to the blood CuZnSOD activity and to plasma total antioxidant power, whereas the serum progesterone levels were positively correlated to CuZnSOD activity and negatively correlated to protein carbonyl groups. Interestingly, the total antioxidant power of plasma was positively correlated to CuZnSOD and glutathione peroxidase activities. Conclusion We conclude that EPT increases blood MnSOD and CuZnSOD activity in postmenopausal women, leading to an increased plasma total antioxidant capacity. This finding may be relevant to the prevention of oxidative stress-related disorders in postmenopausal women.